The Redox Proteome of Thiol Proteins in the Rice Blast Fungus Magnaporthe oryzae - Zhang, Xinrong; Zhang, Zhenhua; Chen, Xiao-Lin (Frontiers in Microbiology, 2021)
Redox modification, a post-translational modification, has been demonstrated significant for many physiological pathways and biological processes in both eukaryotes and prokaryotes. However, little is known about the global profile of protein redox modification in fungi. To explore the roles of redox modification in the plant pathogenic fungi, a global thiol proteome survey was performed in the model fungal pathogen Magnaporthe oryzae. A total of 3713 redox modification sites from 1899 proteins were identified through a mix sample containing mycelia with or without oxidative stress, conidia, appressoria and invasive hyphae of M. oryzae. The identified thiol modified proteins were performed with protein domain, subcellular localization, functional classification, metabolic pathways and protein-protein interaction network analyses, indicating that redox modification is associated with a wide range of biological and cellular functions. These results suggested redox modification plays important roles in fungal growth, conidium formation, appressorium formation, as well as invasive growth. Interestingly, a large number of pathogenesis-related proteins were redox modification targets, suggesting the significant roles of redox modification in pathogenicity of M. oryzae. This work provides a global insight into the redox proteome of the pathogenic fungi, which built a groundwork and valuable resource for future studies of redox modification in fungi.